Universal pattern of RpoB gene mutations among multidrug-resistant isolates of Mycobacterium tuberculosis complex from Africa - Schilke, Kathrin; Weyer, K.; Bretzel, G.; Amthor, Beate; Brandt, J.; Sticht-Groh, V.; Fourie, P. B.; Haas, Walter (The international journal of tuberculosis and lung disease, 1999)
Setting: Multidrug-resistant tuberculosis (MDR-TB) presents an increasing burden in Southern Africa. Rapid diagnostic tests for drug resistance to rifampicin have been developed based on mutation analysis of the RpoB gene. However, geographic differences of underlying mutations have recently been suggested.Objective: Drug-resistant strains of Mycobacterium tuberculosis complex from Africa were analysed for geographic differences in frequency and location of RpoB mutations.Design: A random sample of rifampicin-resistant strains was collected from 87 patients with pulmonary MDR-TB treated in 12 hospitals from six different regions of South Africa. In addition, 18 isolates of M. tuberculosis complex from Namibia, Sierra Leone, and Uganda, including 13 isolates of M. africanum, were analyzed. Point mutations were detected by direct sequence analysis of the RpoB gene.Results: Missense mutations were identified for 91 isolates (87%). Double mutations were present in eight (8%) MDR-TB isolates, two of which carried one mutation outside a previously described diagnostic region. We found no geographic differences regarding the frequency and pattern of single RpoB gene mutations.Conclusion: Our results confirm that molecular genetic analysis of rifampicin resistance based on a core region within the RpoB gene is universally applicable to strains of M. tuberculosis complex from different geographic regions.